2018
DOI: 10.1037/men0000083
|View full text |Cite
|
Sign up to set email alerts
|

“What defines a man?”: Perspectives of African American men on the components and consequences of manhood.

Abstract: What it means to be man is shaped by racial, ethnic, and cultural factors. In this paper, we explore what determines and comprises middle-aged and older African American men's definitions of manhood. Using a thematic approach, we examined the semantic differences noted in the verbs chosen to define a man, the characteristics that were most important to how they saw themselves, and the characteristics that were most important to them to portray to others. Analyzing data from 64 interviews with urban African Ame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
60
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 40 publications
(64 citation statements)
references
References 63 publications
3
60
1
Order By: Relevance
“…Previous reviews have highlighted that more research is needed to better understand how gender can be incorporated in physical activity interventions for African American men ( Bopp et al, 2012 ; Newton et al, 2014 ; Whitt-Glover et al, 2014 ) and there is very little that we know about how to incorporate gender in interventions for Latino men ( Garcia et al, 2017 ; Marquez & McAuley, 2006 ). Given that formative research has identified that there are significant differences in the patterns and social and psychological determinants of physical activity by gender ( Bopp et al, 2006 ; Friedman et al, 2012 ; Griffith, Gunter, & Allen, 2011 ; Hooker, Wilcox et al, 2011 ), Future interventions should explore how being an adult male shapes men’s motivations, attitudes, and preferences to be physically active by considering notions of masculinity, manhood and Machismo ( Arciniega, Anderson, Tovar-Blank, & Tracey, 2008 ; Fragoso & Kashubeck, 2000 ; Griffith, Brinkley-Rubinstein, Thorpe Jr, Bruce, & Metzl, 2015 ; D. M. Griffith & Cornish, 2016 ; Griffith, Gunter, & Watkins, 2012 ; Vandello & Bosson, 2013 ). While given the limitations of the data, we cannot conclude that incorporating gender in targeted interventions makes them more effective than those that do not, future studies should rigorously test if and how considering gender in physical activity among African American and Latino men increases the impact of the intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reviews have highlighted that more research is needed to better understand how gender can be incorporated in physical activity interventions for African American men ( Bopp et al, 2012 ; Newton et al, 2014 ; Whitt-Glover et al, 2014 ) and there is very little that we know about how to incorporate gender in interventions for Latino men ( Garcia et al, 2017 ; Marquez & McAuley, 2006 ). Given that formative research has identified that there are significant differences in the patterns and social and psychological determinants of physical activity by gender ( Bopp et al, 2006 ; Friedman et al, 2012 ; Griffith, Gunter, & Allen, 2011 ; Hooker, Wilcox et al, 2011 ), Future interventions should explore how being an adult male shapes men’s motivations, attitudes, and preferences to be physically active by considering notions of masculinity, manhood and Machismo ( Arciniega, Anderson, Tovar-Blank, & Tracey, 2008 ; Fragoso & Kashubeck, 2000 ; Griffith, Brinkley-Rubinstein, Thorpe Jr, Bruce, & Metzl, 2015 ; D. M. Griffith & Cornish, 2016 ; Griffith, Gunter, & Watkins, 2012 ; Vandello & Bosson, 2013 ). While given the limitations of the data, we cannot conclude that incorporating gender in targeted interventions makes them more effective than those that do not, future studies should rigorously test if and how considering gender in physical activity among African American and Latino men increases the impact of the intervention.…”
Section: Discussionmentioning
confidence: 99%
“…We used a thematic approach, 20 similar to the methods previously used by the research team for analysis of qualitative interview data. 15,[21][22][23] This approach allows for the researchers to identify, analyze and report themes and classifications that relate to the data and helps to discover, organize and describe interpretations of the data. 24 A researcher trained in qualitative data analysis reviewed the transcripts to check for accuracy, familiarized herself with the transcripts and developed the codebook by revising and expanding one that was used in a prior, similar study.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to prior research, we found that our participants conveyed that they understood the sociocultural characteristics that are presumed to be associated with being an adult, La-Precision Lifestyle Medicine Intervention -Griffith et al tino male but they saw the notion of machismo too restrictive. 13,15,25 Rather, they sought to embody and portray characteristics and attributes that were more consistent with the notion of Caballerismo -an aspect of masculinity that focuses on social responsibility, emotional connectedness, and respectability 25 -and familism or a rooting of their life goals and aspirations not in their individual success but that of their family 6,11,26 . The efforts these men described to embody values and goals that are consistent with ideals of Caballerismo and familism, and the prioritizing of their family's needs and goals are laudable, but it also maps onto key barriers to healthy eating and physical activity that have been associated with provider role strain in middleaged and older African American men.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This article presents findings from data collected as part of a larger study that was conducted between March and April 2014; the study aimed to explore the social determinants of middle-aged and older African American men's health behavior and perceptions of manhood. 17,18…”
Section: Methodsmentioning
confidence: 99%